2010
DOI: 10.1259/dmfr/16059055
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic enlargement of mandibular canal as first feature of non-Hodgkin's lymphoma

Abstract: Non-Hodgkin's lymphoma has the propensity to affect non-lymphoid tissue including oral tissue. Primary non-Hodgkin's lymphoma of the mandible mistreated as chronic periodontitis with diffuse enlargement of the mandibular canal and ice-cold numbness is very rarely described in English medical literature. A 57-year-old patient presented with a painful swelling on the left side of the mandible with a clinically chronic periodontitis associated with ice-cold numbness. A panoramic radiograph showed a diffuse unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
0
12
0
4
Order By: Relevance
“…The most common radiological finding in the mandible is a focal or diffuse osteolytic area, generally without edge sclerosis [25,26]. Fusiform widening of the mandibular canal [27][28][29] or the mental foramen may also be observed [25]. In the head and neck, these lymphomas typically present around the age of 40-46 years [26,30] with bony swelling, pain, and sensory disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…The most common radiological finding in the mandible is a focal or diffuse osteolytic area, generally without edge sclerosis [25,26]. Fusiform widening of the mandibular canal [27][28][29] or the mental foramen may also be observed [25]. In the head and neck, these lymphomas typically present around the age of 40-46 years [26,30] with bony swelling, pain, and sensory disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Other radiographic findings include loss of cortical definition, widening of the periodontal ligament, nasal cavity and cavernous sinus enlargement, mental foramen widening, and dilation of the mandibular canal 378. Buric et al,9 and Bertilotto et al10 reported that non-Hodgkin lymphomas of the mandible are rare, but can cause diffuse continuous widening of the mandibular canal (Fig. 1) associated with ice-cold numbness.…”
Section: Resultsmentioning
confidence: 99%
“…Non-Hodgkin lymphoma of the mandible may involve the canal via 2 mechanisms. It may arise from the bone, wrap around the mandibular canal, and infiltrate into it later, or it may arise from the lymphoid tissue of the mandibular canal, grow with neural and perineural spreading, and slowly expand or destroy the surrounding bone over time 9…”
Section: Resultsmentioning
confidence: 99%
“…The differential diagnosis of enlarged foramen and canal is manifold and includes lymphoma (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), peripheral nerve sheath tumor (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), primary sarcoma (35)(36)(37)(38), locally invasive carcinoma of the mucous membranes (39)(40)(41)(42)(43)(44)(45), distant metastasis (46,47), osteomyelitis (48), lipoma (49,50), hemangioma (51), idiopathic (52) and iatrogenic (53) bone defects, as well as various syndromes (54)(55)(56). Unilaterally enlarged mental foramen on a radiograph is suspected to indicate an underlying neoplastic process, predominantly tumors arising from lymphatic or nerve sheath cells…”
Section: Abstract Background: Different Phenomena Can Results In Enlamentioning
confidence: 99%